Biosimilars in the management of neutropenia: focus on filgrastim - Caselli D (Dove Medical Press, 2016)
Désirée Caselli,1 Simone Cesaro,2 Maurizio Aricò1 1Medical Department, Pediatric Unit, Azienda Sanitaria Provinciale Ragusa, Ragusa, 2Department of Pediatrics, Pediatric Hematology Oncology, Azienda Ospedaliera Universitaria Integrata, Verona, Italy Abstract: Advances in chemotherapy and surgery allows the majority of patients to survive cancer diseases. Yet, the price may be a proportion of patients dying of complications due to treatment-induced infectious complications, such as neutropenia. With the aim of decreasing morbidity and mortality related to infectious complications, recombinant human granulocyte colony-stimulating factor (G-CSF), filgrastim, and pegylated filgrastim have been used to reduce time and degree of neutropenia. A biosimilar is a copy of an approved original biologic medicine whose data protection has expired. The patent for filgrastim expired in Europe in 2006 and in the US in 2013. This review analyses the available evidence to be considered in order to design a strategy of use of G-CSF and its biosimilars. The clinical and safety outcomes of biosimilars are well within the range of historically reported data for originator filgrastim. This underscores the clinical effectiveness and safety of biosimilar filgrastim in daily clinical practice. Biosimilars can play an important role by offering the opportunity to reduce costs, thus contributing to the financial sustainability of treatment programs. Keywords: neutropenia, filgrastim, biosimilars, G-CSF, fever, prophylaxis